2021
DOI: 10.3389/fphys.2021.705558
|View full text |Cite
|
Sign up to set email alerts
|

SBP Is Superior to MAP to Reflect Tissue Perfusion and Hemodynamic Abnormality Perioperatively

Abstract: Many articles have reported that intraoperative low mean artery pressure (MAP) or low systolic blood pressure (SBP) impacts on organs’ function and patients’ outcomes perioperatively. On the contrary, what type of blood pressure should be obtained still needs to be clarified. In our paper, we compared the influencing factors of MAP and SBP, and mathematical formula, arterial pulse contour calculation, and cardiovascular physiological knowledge were adopted to discuss how blood pressure can effectively reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Moreover, fluid responsiveness can be evaluated in patients undergoing surgery as PPI reflects cardiac output (23,28). From the perspective of oxygen delivery and tissue perfusion, it is important to maintain adequate cardiac output rather than the more commonly monitored blood pressure, because blood pressure is affected not only by cardiac output, but also by systemic vascular resistance (29). Similarly, in critically ill patients with a low flow state, organ dysfunctions such as AKI are likely to occur due to a decrease in tissue perfusion even if blood pressure is maintained at normal with increased vascular resistance (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fluid responsiveness can be evaluated in patients undergoing surgery as PPI reflects cardiac output (23,28). From the perspective of oxygen delivery and tissue perfusion, it is important to maintain adequate cardiac output rather than the more commonly monitored blood pressure, because blood pressure is affected not only by cardiac output, but also by systemic vascular resistance (29). Similarly, in critically ill patients with a low flow state, organ dysfunctions such as AKI are likely to occur due to a decrease in tissue perfusion even if blood pressure is maintained at normal with increased vascular resistance (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Low SBP re ects poor cardiac reserve, and is found in individuals with serious heart failure or cardiogenic shock [26-28]. In addition, low BP compromises coronary perfusion and enhances ischemia [29,30]. Initial high admission SBP can reduce the rates of cardiogenic shock and heart failure, and is considered a predictor of better prognosis, while elevated SBP caused by acute stress reaction converts to the normotensive condition or decreased level as a result of increased post-load and failing heart, suggesting the loss of its original bene t for STEMI patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Namasivayam et al ( 25 ) directly compared BP at peak exercise workload (upright cycle ergometer) between patients with HFrEF and HFpEF, finding that greater increases in systolic and diastolic BP in individuals with HFpEF. Furthermore, they found that pulsatile BP [the ratio of pulse pressure to systolic BP which indicates the power required to deliver blood to target organs ( 51 )] was positively correlated with both arterial stiffness and SV in patients with HFpEF, but only SV in those with HFrEF. These studies indicate that the excessive BP response during dynamic exercise in patients with HFpEF is likely driven by heightened peripheral vascular dysfunction whereas the pressor response in patients with HFrEF is largely driven by cardiac function.…”
Section: Hemodynamicsmentioning
confidence: 99%